The role of lymph node size and FOXP3+ regulatory T cells in node-negative colon cancer. Issue 5 (22nd November 2016) - Märkl, Bruno; Paul, Beate; Schaller, Tina; Kretsinger, Hallie; Kriening, Bernadette; Schenkirsch, Gerhard
Abstract : Recently, we demonstrated that the intratumoural density of CD3+ and CD8+ T cells is independently prognostic and associated with lymph node (LN) harvest and LN size in node-negative colon cancer. We assumed that FOXP3+ T cells (Tregs) could be inversely associated with these LN features. Therefore, we performed a retrospective immunohistochemical analysis using an already well-characterised collection of stage I/II colon cancer cases. Receiver operating characteristic analysis revealed the optimal cut-off for predicting cancer-related death to be 70 FOXP3+ Tregs/mm 2 at the invasion front. Other than T-stage, none of the relevant histopathological parameters were associated with the density of FOXP3+ cells. In particular, no relation to LN size and count were found. Cancer-specific survival was significantly improved in cases with high densities (115 vs 86 months; p=0.026) in univariable but not in multivariable analysis. In contrast to other cancers, FOXP3+ T cells are associated with a favourable outcome.